Ethnic difference in serum antibodies to oxidized low density lipoprotein in healthy Malaysian subjects (Medical Journal of Indonesia, 2012)
Background: Some populations are more susceptible to atherosclerotic diseases than others. Indians had a higher mortality due to coronary heart disease (CHD) than Chinese and Malays. Antibodies to oxidized low density lipoprotein (Ab-oxLDL) are produced as an immune response to oxidized low density lipoprotein (oxLDL). The difference in prevalence of CHD among the ethnic groups may be related to the immune response. The objectives of this study were to determine the serum Ab-oxLDL levels and lipid profile among the three major Malaysian ethnic groups.Methods: The participants of this study were 150 healthy subjects consisting of 50 Malays, 50 Chinese and 50 Indians. Serum Ab-oxLDL was measured by enzyme immunoassay method. Serum triglycerides and total cholesterol were measured by enzymatic methods. Serum high density lipoprotein cholesterol (HDL-C) was measured by precipitation method and low density lipoprotein cholesterol (LDL-C) was calculated using Friedewald formula.Results: AboxLDL level [adjusted mean (95% of CI)] was highest in Malays [1404 (1202-1607) mU/mL] followed by Chinese [1026 (829-1223) mU/mL] and Indians [954 (744-1163) mU/mL] (P = 0.006) and HDL-C level was highest in Chinese [1.53 (1.44-1.61) mmol/L] followed by Malays [1.44 (1.35-1.53) mmol/L] and Indians [1.35 (1.26-1.45) mmol/L] (P = 0.035).Conclusion: Our results indicate that Ab-oxLDL and HDL-C levels differed by ethnic and AboxLDL may have antiatherogenic properties among Malaysian ethnic groups. (Med J Indones 2012;21:18-22)Keywords: Antibodies to oxLDL, coronary heart disease, ethnic groups, LDL, lipid profile